Für eine Kunst des Unmöglichen. - Dickhoff, Wilfried (Köln : Verlag Kiepenheuer & Witsch Köln, 2001)
Anzinger, Siegfried ; Beuys, Joseph ; Bleckner, Ross ; Bömmels, Peter ; Broodthaers, Marcel ; Clemente, Francesco ; Condo, George ; Dahn, Walter ; Dokoupil, Jiri Georg ; Fautrier, Jean ; Förg, Gunther ; Herold, Georg ; Hodgkin, Howard ; Höller, Carsten ; Kippenberger, Martin ; Marden, Brice ; Oehlen, Albert ; Penck, A.R. ; Richter, Gerhard ; Salle, David ; Schnabel, Julian ; Scholz, Frances ; Schulze, Andreas ; Sherman, Cindy ; Taaffe, Philip ; Trockel, Rosemarie ; van Vliet, Don
Duits
boek